Extension of Sylvatic Circulation of African Swine Fever Virus in Extralimital Warthogs in South Africa - Craig, Anthony F.; Schade-Weskott, Mathilde L.; Harris, Henry J.; Heath, Livio; Kriel, Gideon J. P.; de Klerk-Lorist, Lin-Mari; van Schalkwyk, Louis; Buss, Peter; Trujillo, Jessie D.; Crafford, Jan E.; Richt, Juergen A.; Swanepoel, Robert (Frontiers in Veterinary Science, 2021)
Sylvatic circulation of African swine fever virus (ASFV) in warthogs and ornithodorid ticks that live in warthog burrows historically occurred in northern South Africa. Outbreaks of the disease in domestic pigs originated in this region. A controlled area was declared in the north in 1935 and regulations implemented to prevent transfer of potentially infected suids or products to the rest of the country. However, over the past six decades warthogs have been widely translocated to the south where the extralimital animals have flourished to become an invasive species. Since 2016 there have been outbreaks of ASF in pigs outside the controlled area that cannot be linked to transfer of infected animals or products from the north. An investigation in 2008-12 revealed that the presence of ornithodorid ticks and ASFV in warthog burrows extended marginally across the boundary of the controlled area. We found serological evidence of ASFV circulation in extralimital warthogs further south in the central part of the country.